Validation of the ductile fracture modeling of CGI at quasi-static loading conditions. (September 2021) - Razanica, Senad; Josefson, Lennart B; Larsson, Ragnar; Sjögren, Torsten
Fracture modeling and experimental validation of Compacted Graphite Iron (CGI) specimens loaded under quasi-static conditions at room temperature are considered. Continuum damage mechanics coupled to plasticity is adopted to describe the evolution of damage. The damage production is based on a recently developed rate dependent damage evolution law, where the damage–plasticity coupling is modeled based on a damage driving energy that involves both stored energy and plasticity contributions. To describe ductile fracture accounting for stress triaxiality on the damage initiation, the inelastic contribution to the damage driving energy is controlled by the Johnson-Cook failure criterion. Three different damage models are defined based on elastic/inelastic damage driving energies. The damage models are validated against experiments on a set of notched specimens made of CGI with different notch geometries, where the global force-displacement curves and corresponding strain fields are obtained using digital image correlation technology. It is shown from the testing and the simulations that plastic strains generally need to be accounted for in order to properly describe the different failure processes of the CGI specimens. In addition, the ductile damage model is shown to more accurately predict the experimental force-displacement response as compared to the more simplistic stress drop, element deletion technique.